Growth Patterns and Mortality of Lobster Panulirus ornatus from the Catch of Bottom Gill Net Fishers in the Western Waters of Tarakan Island - Agus Indarjo; Gazali Salim; Thonas Indra Maryanto; Ngungut; Laurha Annisa Linting; Muhammad Firdaus; Rozi; Rukisah (Bogor Agricultural University, Indonesia, 2023)
Large-bodied Panulirus ornatus lobsters are economically important because they are an aquatic biota. It is one of the most important commodities in the city of Tarakan. The aim is to analyze the growth patterns and mortality of P. ornatus from the West Waters of Tarakan City. Method using a quantitative descriptive. The purposive sampling method was used by dragging the gill net fishing gear to the P. ornatus lobster ground area, and the collection was carried out 16 times in 7 months (December 2021-July 2022). The results of P. ornatus showed that the male sex ratio was higher than the female. The growth model was allometrically negative, and the criteria for the condition index were fat and thin. The growth pattern of Model Von Bertalanffy males is slower than females. However, the growth rate to achieve asymptotic growth for males is faster than for females. The total mortality, catch mortality, and exploitation rate of males was higher than females. However, the mortality of the female nature was higher than that of males. P. ornatus should be managed in the waters of West Tarakan using the domestication and restocking technique to increase sustainability.